Ulnar nerve lesions associated with the carpal tunnel syndrome - Sedal, L. (1973)
Electrophysiological studies were performed on median and ulnar nerves in 234 cases of carpal tunnel syndrome. Abnormalities of the ulnar nerve sensory action potential were found in 39·3% of cases. The amplitude of the ulnar nerve sensory action potential was related to the amplitude of the median nerve sensory action potential, and to the median nerve motor conduction velocity in the forearm. The findings suggest that in a significant proportion of patients with carpal tunnel syndrome, a more generalized subclinical neuropathy may be present.